Selection, optimization and characterization of molecular tests for the detection of Tobacco ringspot virus (TRSV). (18th April 2019) - Renvoisé, J. P.; Chambon, F.; Gleize, M.; Pradeilles, N.; Garnier, S.; Rolland, M.
Abstract : The aim of the study was to select, optimize and characterize RT‐PCR tests for the detection of Tobacco ringspot virus (TRSV) in post‐entry quarantine. Among five different tests, the Poojari et al . ( Journal of Virological Methods 235, 112–118) and Jossey & Babadoost ( Plant Disease 90, 1361) conventionnal RT‐PCR tests were chosen and optimized for this purpose. Ten TRSV isolates, 17 healthy plants from the genera Vitis, Prunus and Malus, four other Nepoviruses or Secoviridae isolates and serial dilutions of three TRSV isolates were used for the complete characterization of the optimized tests. In the tested conditions, the Poojari and Jossey & Babadoost tests respectively showed 100% and 95% inclusivity, 100% and 100% exclusivity, 100% and 96.4% analytical specificity, 100% and 100% diagnostic specificity, [10 −7 ; 10 −1 ] and [10 −8 ; 10 −2 ] limit of detection dilution factors (analytical sensitivity), 91.1% and 90.0% repeatability, 90.3% and 91.1% reproducibility and 100% and 100% selectivity. Due to its higher inclusivity, the optimized Poojari test is recommended for the detection of TRSV isolates for post‐entry quarantine purposes, but can also be used for global surveys. The optimized Jossey & Babadoost test showed the best analytical sensitivity, suggesting that combining both tests can further enhance detection. Sélection, optimisation et caractérisation de tests moléculaires de détection du Tobacco ringspot virus (TRSV): L'objectif de l'étude était de sélectionner, optimiser et caractériser des tests de RT‐PCR pour la détection du Tobacco ringspot virus (TRSV) dans le cadre de la quarantaine végétale post‐entrée. Parmi cinq tests différents, les tests en RT‐PCR conventionnelle issus de Poojari et al . ( Journal of Virological Methods 235, 112–118) et de Jossey & Babadoost ( Plant Disease 90, 1361) ont été sélectionnés et optimisés. Dix isolats de TRSV, dix‐sept plantes saines des genres Vitis, Prunus et Malus, quatre autres isolats de Nepovirus ou de Secoviridae et des dilutions en série de trois isolats de TRSV ont été utilisés pour la caractérisation complète des tests optimisés. Dans les conditions testées, les tests de Poojari et Jossey & Babadoost ont montré respectivement une inclusivité de 100% et 95%, une exclusivité de 100% et 100%, une spécificité analytique de 100% et 96, 4%, une spécificité diagnostique de 100% et 100%, une limite de détection (sensibilité analytique) définie par les intervalles [10 ‐7 ; 10 ‐1 ] et [10 ‐8 ; 10 ‐2 ], une répétabilité de 91, 1% et 90, 0%, une reproductibilité de 90, 3% et 91, 1% et une sélectivité de 100% et 100%. En raison de sa meilleure inclusivité, le test optimisé de Poojari est recommandé pour la détection des différents isolats de TRSV dans un cadre de quarantaine post‐entrée mais peut également l'être pour une surveillance globale. Le test optimisé de Jossey & Babadoost ayant montré une meilleure sensibilité analytique, une amélioration de la détection peut être obtenue en combinant l'utilisation des deux tests. Выбор, оптимизация и описания молекулярных тестов для выявления вируса кольцевой пятнистости табака (ВКПТ): Целью исследования был выбор, оптимизация и описание ПЦР‐теста в реальном времени для выявления вируса кольцевой пятнистости табака (ВКПТ) при карантине после ввоза. Среди пяти различных ПЦР тестов в реальном времени для этой цели были выбраны и оптимизированы традиционные тесты Poojari et al . ( Journal of Virological Methods 235, 112–118) и Jossey & Babadoost (2006). 10 изолятов ВКПТ, 17 здоровых растений из родов Vitis, Prunus и Malus, четыре других изолята из групп неповирусов или Secoviridae и серийные разбавления трех изолятов ВКПТ иcпoльзoвaлиcь для пoлнoгo oпиcaния. В условиях испытаний тесты Poojari и Jossey & Babadoost ( Plant Disease 90, 1361) показали соответственно 100 % и 95 % инклюзивности, 100% и 100% эксклюзивности, 100% и 96, 4% аналитической специфичности, 100% и 100% диагностической специфичности, пределы селективности обнаружения факторов разбавления [10‐7 ; 10‐1 ] и [10‐8 ; 10‐2 ] (аналитическая чувствительность), 91, 1% и 90, 0% повторяемости, 90, 3% и 91, 1% воспроизводимости и 100% и 100% селективности. В связи с более высокой инклюзивностью, оптимизированный тест Poojari рекомендуется для выявления изолятов ВКПТ при карантине после ввоза, но также может быть использован для глобальных обследований. Оптимизированный тест Jossey & Babadoost показал наилучшую аналитическую чувствительность, что позволяет предположить, что сочетание обоих тестов может еще больше улучшить выявление.